Hepatoprotective Effects of Nasturtium Officinale and Allium Polyanthum Extracts on CCL4- Induced Hepatic Damage In Albino Rats - K.Rostam, Shkar Rzgar; Ibrahim, Zana Hassan; Mala, Rebaz Rebwar; Abdul, Soran Qadir (Kurdistan Journal of Applied Research, 2022)
The aim: This study was designed to explore the potential hepatoprotective effects of Nasturtium officinale and Allium polyanthum plant extracts against CCl4-induced hepatic injury in rat model. Methods: Thirty healthy male albino rats were equally divided into 5 groups: Normal control (NC), Positive control (Pos-C), Nasturtium officinale extract (NOE), Allium polyanthum extract (APE), and NOE + APE. The animals were fed with a standard diet and distilled water ad libitum. Except for NC, all other groups were exposed to CCl4 at every 72 hours for 3 weeks to induce hepatic damage. Corresponding treatments were established to the respective groups during study period. Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Alkaline phosphatase (ALP), Total serum bilirubin (TSB), Total protein (TP), Albumin (ALB) and malondialdehyde (MDA) were measured in serum at the end of the study. Histopathological analysis of the liver sections was also determined. Results: CCl4-treated rats were showed significant increase (p < 0.05) in the levels of serum enzyme activities (AST, ALT, & ALP), TSB and MDA; reflecting the hepatocellular damage caused by CCl4 compared with NC rats, whereas the levels of TP and ALB were decreased. Furthermore, the histological examination of liver tissues showed that CCl4 triggered several histological variations in the liver tissues. Treatments of NOE and APE along with CCl4 for 3 weeks significantly (P<0.05) improved the CCl4-induced changes in serum biochemical parameters and liver histology as compared to Pos-C rats indicating the protection of hepatic cells. Conclusion: Treatments of NOE and APE either in separate or in combination have shown significant improvement in CCl4-induced hepatopathy in experimental rats as evidenced by observed results in serum and hepatic histopathological examinations